Community participation in realising the digital reading corner programme: A case study in Tebing Tinggi City, Indonesia - Rangkuti, Zoraya Alfathin; Rangkuti, Mohammad Ridwan; Bahri, Saipul; Setiawan, Ferry; Lubis, Zulkifli (Research Journal in Advanced Humanities, 2025)
The decreasing interest in reading books has resulted in books being replaced by digital media. Changes in community behavior in the era of disruption occur because people are more interested in information obtained through online news that is spread on various websites and social media. This study aims to determine community participation in the implementation of Pondok Baca Digital (Henceforth POCADI) or the Digital Reading Corner program in Tebing Tinggi City which focuses on community involvement in utilizing the POCADI program to increase reading interest and digital literacy in Tebing Tinggi City. This research used descriptive qualitative research methods. The data collection techniques were interviews, observation and documentation. The results show that the POCADI program still has not shown a positive impact in increasing interest in reading and literacy in the community. Community participation in this program has not been carried out optimally at each stage. Especially at the implementation stage, where the community has not fully utilized POCADI as a reading place that supports an increase in interest in reading and digital literacy in the community.